Clinical study of the safety and effectiveness of a novel over-the-counter bleaching tray system - Ghalili KM; Khawaled K; Rozen D; Afsahi V (Dove Medical Press, 2014)
K Michael Ghalili,1 Kamal Khawaled,2 Doran Rozen,2 Veda Afsahi3 1Department of Prosthodontics, New York University College of Dentistry, New York, NY, USA; 2Department of R&D; Department of Clinical Affairs, Syneron Beauty, Ltd, Yokneam, Israel; 3Veda Faith Afsahi Inc., Fountain Valley, CA, USA Abstract: We investigated color change, gingival irritation, and tooth sensitivity in patients undergoing at-home vital tooth bleaching with a novel over-the-counter bleaching tray system. Tooth color shade in anterior teeth, supragingival plaque and gingivitis in Ramfjord teeth, as well as visual assessment of teeth gingival tissues and mucosa were evaluated in-office prior to treatment, after two consecutive applications of the 9% hydrogen peroxide bleaching product, after eight applications (10 minutes/day for 3 days at home), and after ten applications (50 minutes exposure over 5 days). Color stability was evaluated at 3 months after completing the treatment regimen. Over-the-counter bleaching products can be used by the patient at home without dentist supervision, but are frequently associated with gingival irritation and tooth sensitivity despite low concentrations of peroxide agents. Our investigations showed that the treatment is tolerable and safe with a low incidence of adverse effects. Any adverse effects associated with use of the whitening gel and tray are temporary, easily controlled, and often disappear within minutes of treatment. Statistical analysis revealed significant improvement in teeth whitening following treatment (mean color change of seven shades) and at three months after treatment. Keywords: at home tooth-whitening, hydrogen peroxide teeth whitening, over-the-counter tooth-whitening, teeth bleaching